A Comparison of Two Surgical Techniques for the Second Stage of Brachiobasilic Arteriovenous Fistula Creation. Issue 6 (21st November 2016) - Mauro, Raffaella; Pini, Rodolfo; Bianchini Massoni, Claudio; Donati, Gabriele; Faggioli, Gianluca; Gargiulo, Mauro; Freyrie, Antonio; La Manna, Gaetano; Stella, Andrea
Abstract: Two‐stage transposed brachiobasilic arteriovenous fistula is a common procedure after brachiobasilic fistula (BBF) creation. Different techniques can be used for basilic vein transposition but few comparative literature reports are available. The aim of our study was to compare two different techniques for basilic vein transposition. The first maintains the BBF anastomosis and the basilic vein is placed in a subcutaneous pocket (BBAVF). The second transects the basilic vein at the BBF anastomosis and tunnels it superficially, with a new BBF in the brachial artery (BBAVFTn). From 2009 to 2014, all patients who underwent basilic vein superficialization were treated by one of the two techniques, recorded in a dedicated database and retrospectively reviewed. The surgeon chose the technique on the basis of personal preference. The two techniques were compared in terms of perioperative complications, length of hospital stay, time of cannulation, ease of cannulation, and long‐term patency. Eighty patients were included in the study: 40 (50%) BBAVF and 40 (50%) BBAVFTn. Length of hospital stay was similar in the two groups (median [interquartile range–IQR] 3(2) [BBAVF] vs. 2(1) [BBAVFTn], P  = 0.52, respectively). BBAVFTn was associated with a lower hematoma incidence (1/40 [2.5%] vs. 15/40 [37.5%], P  = 0.01), shorter first cannulation time (median IQR: 11(10) vs. 23(8) days, P  = 0.01) and easier cannulation compared with BBAVF (32/40 [80%] vs. 15/40 [37.5%], P  < 0.001). Median (IQR) follow‐up was 16(7) months. No statistical differences in terms of primary and assisted primary patency were found in BBAVFTn vs. BBAVF (at 24 months 91(5) vs. 71(7), P  = 0.21 and 93(6) vs. 78(8), P  = 0.33, respectively). Patients who underwent BBAVFTn surgery showed fewer surgical complications, better dialytic performance, and easier cannulation compared with those submitted to BBAVF.